2009
DOI: 10.1111/j.1540-8175.2009.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Doppler‐Derived Myocardial Performance Index in Patients with Impaired Left Ventricular Relaxation and Preserved Systolic Function

Abstract: MPI was increase in patients with hypertension, diastolic dysfunction, and normal ejection fraction but was not superior to IRT to detect impaired LV relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…MPI of the left ventricle was increased at baseline, which is in line with a recent study comparing hypertensive patients with normal control subjects. 28 We demonstrated that in hypertensive patients MPI of the right ventricle is also increased. A study in patients with systemic sclerosis and other connective tissue diseases showed that an elevated MPI could increase the accuracy of echocardiography in prediction of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 94%
“…MPI of the left ventricle was increased at baseline, which is in line with a recent study comparing hypertensive patients with normal control subjects. 28 We demonstrated that in hypertensive patients MPI of the right ventricle is also increased. A study in patients with systemic sclerosis and other connective tissue diseases showed that an elevated MPI could increase the accuracy of echocardiography in prediction of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 94%
“…The isovolumetric contraction time (ICT) was measured from the onset of closure of the mitral valve until the onset of the opening of the aortic. The ejection time (ET) was calculated from the opening until the closure of the aortic valve (10). All parameters were measured from the same cardiac cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin D affects left ventricular structure by increasing left ventricle mass and myocardial contractility by affecting calcium flux and calcium homeostasis (9). Left ventricle (LV) myocardial performance index (MPI) combines the indices of contract ion and relaxation in an overall index of LV function (10, 11). We hypothesized that vitamin D level may be associated with LV function and geometry.…”
Section: Introductionmentioning
confidence: 99%
“…21 The length of IRT is not shortened with increasing heart rates (82 ms at 66 beats/min, 103 ms at 72 beats/min). 20 The length of diastasis tends to be suffi ciently longer than the temporal resolution of SSCT in patients with low heart rates and seems to be long enough for image reconstruction. The length of diastasis tends to become shorter than the temporal resolution of SSCT with an increasing heart rate, and the diastolic phase may not be used for image reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Generally, the isovolumetric contraction time (ICT) is approximately 30 ms, which is too short a period for image reconstruction. 20 Therefore, the isovolumetric relaxation just after the end of systole and diastasis in diastole are most frequently used for image reconstruction. Furthermore, in the nonproportional shortening of diastasis with higher patient heart rates, the length of diastasis becomes shorter than the isovolumetric relaxation time (IRT).…”
Section: Discussionmentioning
confidence: 99%